The Role of Pancasila in Building Tolerance Between Religious Communities in Multicultural Society - Hidayah, Nuri; Handayani , Nuri; Intani, Aprilia; Khairunnisa, Khairunnisa; Elsa Putri, Wetria; Silvina, Silvina; Putri, Nayla Aurelia (Jurnal Edukasi Terkini, 2025)
This study aims to explore the role of Pancasila in building interfaith tolerance in Indonesia's multicultural society through the literature review method. By analysing various sources such as reference books, scientific journals, and relevant articles, this research identifies and understands how Pancasila values. Such as gotong royong, social justice, and religious freedom are applied in daily life to create harmony among various religious groups. The results of the literature review show that consistent application of Pancasila values can strengthen tolerance and reduce religious-based conflicts. Challenges such as radicalism and discrimination are faced with collaboration from various elements of society, including education, interfaith dialogue, and law enforcement. This research provides insight into the effectiveness of Pancasila as a foundation in building an inclusive and harmonious society amidst diversity.